2013
DOI: 10.1287/orsc.1120.0781
|View full text |Cite
|
Sign up to set email alerts
|

Getting Ahead or Getting Along? The Two-Facet Conceptualization of Conscientiousness and Leadership Emergence

Abstract: W e propose a theoretical process model of the social construction of leadership that sheds light on the relationship between conscientiousness and leadership emergence. The socioanalytic theory of personality is invoked to hypothesize different mediational paths linking the two facets of conscientiousness, achievement striving and duty, with leadership emergence. We tested the theoretical model with data from 249 employees matched with data from 40 of their coworkers and 40 supervisors employed in a Fortune 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 119 publications
(184 reference statements)
1
107
0
Order By: Relevance
“…Although the primary focus of this study was on gender, we controlled for extraversion, conscientiousness, and agreeableness because prior research has shown that these relate to both leadership emergence and effectiveness (DeRue et al, 2011; Ensari et 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 al., 2011; Grant, Gino, & Hofmann, 2011;Judge et al, 2002;Marinova, Moon, & Kamdar, 2013). Thus, any effects detected in this study for gender cannot be attributed to potential personality differences between the men and women in this sample.…”
Section: Measures: Control Variablesmentioning
confidence: 65%
“…Although the primary focus of this study was on gender, we controlled for extraversion, conscientiousness, and agreeableness because prior research has shown that these relate to both leadership emergence and effectiveness (DeRue et al, 2011; Ensari et 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 al., 2011; Grant, Gino, & Hofmann, 2011;Judge et al, 2002;Marinova, Moon, & Kamdar, 2013). Thus, any effects detected in this study for gender cannot be attributed to potential personality differences between the men and women in this sample.…”
Section: Measures: Control Variablesmentioning
confidence: 65%
“…Whether or not this dominance behaviour actually leads to more status is unclear. There is research showing that dominant individuals exercise more influence in a group, because they are seen as more competent (Anderson and Kilduff, 2009), and competitive people are more likely to emerge as leaders (Marinova et al, 2013). However, there seems to be a trade-off regarding leadership, as high basal testosterone levels are also associated with less emphatic accuracy (Ronay and Carney, 2013) and less prestige (Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is a compound trait comprised of achievement striving and planfulness. In previous research, achievement striving has been found to predict positive employee outcomes such as commitment (Moon 2001), leadership emergence (Marinova et al 2013) and supervisory ratings of potential and overall job and task performance (Thomason et al 2011). The other trait component that comprises strategic independence, planfulness, has been found to predict positive student outcomes.…”
Section: Introductionmentioning
confidence: 90%
“…The current study builds on narrow-band trait research by focusing on one facet of conscientiousness, achievement striving (Costa and McCrae 1992), which is a dimension of strategic independence. There is strong emerging support in the personality research literature for studying underlying facets associated with conscientiousness in the prediction of job performance and other positive achievement outcome variables (Marinova et al 2013;Thomason et al 2011). Achievement striving is defined as having high levels of aspiration, willingness to work hard to achieve goals, purposefulness and a sense of direction in life (Costa and McCrae 1992).…”
Section: Strategic Independencementioning
confidence: 99%
See 1 more Smart Citation